2023
DOI: 10.1002/cbdv.202201231
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inhibition and Antioxidant Activities of Asparagus officinalis L. and Analysis of Its Phytochemical Content by LC/MS/MS

Abstract: In the study, water, ethanol, methanol, dichloromethane, and acetone extracts of Asparagus officinalis L. were obtained by maceration. DPPH⋅, ABTS⋅+, FRAP, and CUPRAC methods determined the antioxidant capacities of all extracts. Moreover, the in vitro effects of extracts on acetylcholinesterase (AChE), butyrylcholinesterase (BChE), carbonic anhydrase (CA)‐I, CA‐II and α‐Glycosidase were investigated. At a 10 μg/ml concentration, the extract with the highest Fe3+ reduction capacity was ethanol (AE), and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…They note that the extraction yield is significantly influenced by solvent composition, temperature and extraction time and propose that that optimal extraction occurs using 50% ethanol as a solvent with a liquid-solid ratio of 30:1, extraction temperature of 80 • C, and time of two hours. Phytochemical analysis using liquid chromatography/mass spectrometry (LC/MS)-MS by Comakli et al [12] identified three phytochemicals in acetone extract from the aerial parts of A. officinlis: p-coumaric acid, rutin, and 4-hydroxybenzoic acid (284.3 ± 4.0; 135.4 ± 8.2, and 102.1 ± 5.5 µg analyte/g extract, respectively).…”
Section: Morphology and Phytoconstituents Of A Officinalismentioning
confidence: 99%
See 2 more Smart Citations
“…They note that the extraction yield is significantly influenced by solvent composition, temperature and extraction time and propose that that optimal extraction occurs using 50% ethanol as a solvent with a liquid-solid ratio of 30:1, extraction temperature of 80 • C, and time of two hours. Phytochemical analysis using liquid chromatography/mass spectrometry (LC/MS)-MS by Comakli et al [12] identified three phytochemicals in acetone extract from the aerial parts of A. officinlis: p-coumaric acid, rutin, and 4-hydroxybenzoic acid (284.3 ± 4.0; 135.4 ± 8.2, and 102.1 ± 5.5 µg analyte/g extract, respectively).…”
Section: Morphology and Phytoconstituents Of A Officinalismentioning
confidence: 99%
“…Recently, the antioxidant activities of water, methanol, ethanol, chloroform, and acetone extracts of aerial parts of A. officinalis have been studied using various methods, including ABTS, DPPH, ferric ion reducing antioxidant power (FRAP), and Cu 2+ ion reduc-tion (CUPRAC). Comakli et al [12] found the ethanol extract (10 µg/mL) to demonstrate the highest Fe 3+ reduction capacity, and acetone extract (10 µg/mL) displayed the greatest Cu 2+ reduction potential. Moreover, all tested extracts appeared to inhibit the activity of the enzymes acetylcholinesterase, butyrylcholinesterase, carbolic anhydrase and α-glucosidase, which are involved in various diseases, in vitro; it was also found that consumption of A. officinalis can support the treatment of certain diseases, including glaucoma, epilepsy, Alzheimer's disease, and type 2 diabetes.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation